Beyond news broadcasting: television for peace making in South-Western Nigeria (2018)
Discourses on peace building roles of social institutions have become very core to achieving human security and egalitarian society. The role of the media has moved beyond reporting and providing early warning insight into human security threats to getting practically involved in Peace making and Peace building. This paper explores the role of television in Peace making activities and in providing platform for alternative dispute resolution at the grassroots. Five local television programmes, Olowogbogboro of Ogun State Television, Ijoko Ojogbon of Ondo state Television, So daa bee? of Oyo State Television, Mo gb’ejo mi de of Lagos State Television and Majiya gbe if Osun State Television served as case studies. The Social responsibility theory of the press served as framework while qualitative data were collected through in-depth interviews of program producers, program panel members and disputing parties. Observations of live studio recordings of the five selected programs were done while analyses f program diaries were carried out. It is established that television programming is contributing to culturally relevant, flexible, accommodating and cheaper alternative Peace making processes and conflict resolution, complementing the formal justice system that is inaccessible to the poor and overwhelmed by civil and criminal cases. The programs deserve adequate support and encouragement